Age-period-cohort analysis of gender differential trends in incidence and mortality of non-Hodgkin lymphoma in China, 1990-2019 - Yao, Yuanyuan; Liu, Hui; Zhao, Fei; Zhang, Shengli; Liu, Xingrong (Frontiers in Oncology, 2023)
Background: Non-Hodgkin lymphoma (NHL) is one of the dominant malignancies in the hematological system. This study estimated secular trends in NHL incidence and mortality from 1990 to 2019 and provided comprehensive evaluations of potential age, period, and cohort effects. Methods: Age-period-cohort (APC) models were used to analyze changes in NHL incidence and mortality with age, period, and birth cohort effects based on data from the Global Burden of Disease Study 2019. Results: The age-standardized incidence rates (ASIR) of NHL rose by 144.6% and age-standardized mortality rate (ASMR) rose by 27.5% from 1990 to 2019. Local drift for incidence was greater than 0 (p < 0.05) for both genders in each age group. Local drift for mortality rates were greater than 0 (p < 0.05) for males aged 20 to 89 years and females aged 60 to 84 years and less than 0 (p < 0.05) for females aged 20 to 50 years. Period rate ratio (RR) and cohort RR of NHL incidence in China showed an increasing trend, while the trend of male and female mortality was not consistent. Conclusions: NHL incidence and mortality rates have been increasing in China over the past three decades. Males and older individuals were at high risk for NHL. Thus, attention to the prevention and therapy of NHL would be essential to lessen the disease burden of NHL.